(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
State cooperation in space research is one of the priority topics of international space law. The calls for international cooperation contained in many documents on space law are aimed at preventing the transformation of outer space into a conflict zone. Space cooperation is a very effective way of the confidence-building, because it can reduce mutual suspicion, increase mutual trust and achieve mutual benefits. The space has become a powerful thruster of scientific and technological progress. This trend is one of many indicators pointing to the global trend involving key actors making a decision to make space activities a priority. Many countries come to the understanding that international cooperation is the best means of realization of space programs. At that, the issue of forms of such cooperation gains special importance. It is difficult to think of international space law and the governance of international affairs in isolation from international organizations. The states have joined their efforts in the framework of international organizations with the aim of cooperation in the space sector. In this article we will try to analyze the legal foundations of international cooperation of states in outer space exploration. Key words: international space law, legal regime of the outer space, international responsibility of states, space activities of mankind, global role players.